Peningkatan Hasil Belajar PKn Melalui Pembelajaran Kooperatif Model STAD (Student Teams Achievement Division) pada Siswa SD Negeri 8 Darul Hikmah - Munawir Syam (Indonesian Journal of Teaching and Teacher Education, 2022)
The purpose of this research is to discover how to improve PKn learning outcomes using the STAD (Student Teams Achievement Division) cooperative learning method. STAD is a Cooperative Learning approach that emphasizes activities and interactions between students in order to motivate and assist one another in mastering the subject matter. This study employs three action research cycles, each of which has four stages: design, activities and observations, reflection, and revision. Formative test results and observation sheets of teaching and learning activities were used to collect data. Formative test results and observation sheets of teaching and learning activities were used to collect data. The results showed that there was an increase from cycle I to cycle III, with cycle I increasing by up to 68.2 percent, cycle II increasing by up to 81.58 percent, and cycle III increasing by up to 94.74 percent. As a result, for the 2018-2019 school year, the STAD cooperative learning method can have a positive effect on the achievement and learning motivation of Class V students at SDN 8 Darul Hikmah. As a result, this learning model can be used as an alternative for Civics education.